2017
DOI: 10.1302/0301-620x.99b6.bjj-2016-0577.r2
|View full text |Cite|
|
Sign up to set email alerts
|

Lumbar surgery prior to total hip arthroplasty is associated with worse patient-reported outcomes

Abstract: Lumbar spinal surgery prior to THA is associated with less reduction of pain, worse health-related quality of life, and less satisfaction one year after THA. This is useful information to share in the decision-making process and may help establish realistic expectations of the outcomes of THA in patients who also have previously undergone lumbar spinal surgery. Cite this article: 2017;99-B:759-65.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 30 publications
3
44
0
5
Order By: Relevance
“…We recently demonstrated that LBS prior to THR was associated with worse HRQol, more pain, and less satisfaction 1 year following THR . We found that time between surgeries did not influence outcomes, which is consistent with the present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We recently demonstrated that LBS prior to THR was associated with worse HRQol, more pain, and less satisfaction 1 year following THR . We found that time between surgeries did not influence outcomes, which is consistent with the present study.…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, this and our previous work represent the first efforts to combine hip arthroplasty register data with spine register data. To answer the question of where to perform surgery first, we advise a follow‐up study investigating PROMs following THR and LBS, respectively, when there has also been previous surgery performed in the other location respectively within a relatively short period of time.…”
Section: Discussionmentioning
confidence: 98%
“…После дообследования пациентам диагностирован ОА ТБС [12,13] и проведено второе хирургическое вмешательство. В таких случаях итоговый результат оказался хуже, так как нейрохирургическое лечение пациентам исходно не требовалось [3]. Обратная ситуация, когда болевой синдром сохранялся после тотального эндопротезирования ТБС из-за недооценки вклада патологии поясничного отдела позвоночника, отмечалась в 29% случаев [8].…”
Section: Discussionunclassified
“…Основную сложность в диагностике КВС представляют выявление источника боли и последующий выбор метода лечения у пациентов, так как при неправильно выбранной тактике «первой операции» второе оперативное вмешательство зачастую имеет худшие результаты [3,4]. Жалобы на боль в ягодичной области, бедре, паху и/или области коленного сустава, иногда с нарушением походки, боль в поясничном отделе позвоночника являются типичными как для пациентов с ОА ТБС, так и для больных с дегенеративными изменениями поясничного отдела позвоночника [5].…”
unclassified
“…Further, patients with improvement in LBP also had a significant difference in the amount of overall improvement (51.96 vs. 44.58, P < .000). Relatedly, a study assessing outcomes following hip arthroplasty reported worse pain (95% confidence interval [CI] 2.57 to 6.12), quality of life measures (95% CI ‐0.112 to −0.066) and satisfaction (95% CI 4.05 to 8.02) in patients who had previous lumbar spine surgery. As a whole, these studies suggest that overall, hip arthroplasty helps improve lumbar spine related pain and function …”
Section: Complex Subgroupmentioning
confidence: 99%